2010
DOI: 10.1016/j.avsg.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index: Surgical Site Infections and Mortality after Lower Extremity Bypass from the National Surgical Quality Improvement Program 2005–2007

Abstract: Objectives-Patients undergoing lower extremity bypass are at high risk for surgical site infections (SSI). We examine lower extremity bypasses by graft origin and body mass index (BMI) classification to analyze differences in postoperative mortality and SSI occurrence. Methods-The 2005-2007National Surgical Quality Improvement Program (NSQIP), a multiinstitutional risk-adjusted database, was queried to compare perioperative mortality (30-day), overall morbidity, and SSIs after lower extremity arterial bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
4
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 18 publications
6
114
4
1
Order By: Relevance
“…Higher ASA class was a risk factor for SSI among our laparotomy patients, confirming prior reports. [19][20][21][22][23][24] Potential explanations for the link between SSI and obesity include increased thickness of poorly vascularized subcutaneous adipose tissue layer, local tissue trauma resulting from excessive retraction, and higher bacterial density at abdominal or groin creases. Therefore, careful attention to closure technique and proper choice and dosing of prophylactic antibiotics might be helpful in lowering the incidence of SSI in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher ASA class was a risk factor for SSI among our laparotomy patients, confirming prior reports. [19][20][21][22][23][24] Potential explanations for the link between SSI and obesity include increased thickness of poorly vascularized subcutaneous adipose tissue layer, local tissue trauma resulting from excessive retraction, and higher bacterial density at abdominal or groin creases. Therefore, careful attention to closure technique and proper choice and dosing of prophylactic antibiotics might be helpful in lowering the incidence of SSI in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obesity has increased the risk of SWI after peripheral artery surgery in other studies with smaller number of patients with an OR varying between 1.7 and 6.08 (11,13,23,25,39). In addition, morbid obesity (body mass index (bmI) ≥ 40 kg/m 2 ) has been found to be an independent risk factor for SWI after open aortic aneurysm repair with an OR of 2.6 (16).…”
Section: Risk Factors For Swi After Lower Limb Vascular Surgerymentioning
confidence: 97%
“…(OR = 1.7, 95% CI: 1.4-2.1) [16]. In addition, it has been reported that diabetes predisposes patients for SSI as the glucose level in the blood diminishes immune function [17,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Class IV dirty/infected Class I or II (clean or clean-contaminated); Class III or IV (contaminated or dirty/infected) ASA class 16 1. ASA 1 (no disturb) 2.…”
Section: Development Of Risk Scoring Tool To Predict Surgical Site Inmentioning
confidence: 99%
See 1 more Smart Citation